Peran Motivasi Spiritual dan Komitmen Berkelanjutan dalam Peningkatan Kinerja Sumber Daya Manusia - Novitawati, Novitawati; Mulyana, Mulyana (VISA: Journal of Vision and Ideas, 2025)
The importance of disaster and fire management in the West Kotawaringin Regency area requires the Regional Government, especially the Fire and Rescue Service and the West Kotawaringin Regency Production Forest Management Unit to ensure the improvement of disaster and fire management performance, especially the improvement of Human Resources. One of the influencing factors is spiritual motivation and sustainable commitment. This research aims to describe and analyze the influence of spiritual motivation and continuance commitment on human resource performance and how spiritual motivation affects the continuance commitment of disaster and fire management officers. This research used quantitative method (Explanatory research). The population of this research is disaster and fire management officers at the Fire and Rescue Service and the Production Forest Management Unit of West Kotawaringin Regency. The determination of the number of samples (sample size) uses a census, where the number of population is equal to the number of samples, which is 82 respondents who work in the Fire and Rescue Service and the Production Forest Management Unit of West Kotawaringin Regency and the entire sample questionnaire results can be processed. The data analysis technique used in this study is statistical analysis of data using the PLS-SEM method. The results of this research show that spiritual motivation and continuous commitment have a positive and significant effect on human resource performance. Furthermore, spiritual motivation has a positive and significant effect on sustainable commitment.